A novel non-sequencing approach for rapid authentication of Testudinis Carapax et Plastrum and Trionycis Carapax by species-specific primers. Issue 4 (18th April 2018) - Yang, Huan; Yu, Pingtian; Lu, Yi; Jiao, Zhaoqun; Chen, Liqun; Zhou, Ying; Shen, Yuping; Jia, Xiaobin
Abstract : A novel non-sequencing approach was developed to detect short DNA fragments ( ca 100 bp) for rapid authentication of two natural products, namely Testudinis Carapax et Plastrum and Trionycis Carapax, based on the difference in mitochondrial genome. Five specifically designed primer reactions were established to target species for reliable identification of their commercial products. They were confirmed to have a high level of inter-species-specificity and good intra-species stability. The limit of detection was estimated to be 1 ng of genomes for all of five assays. Also, the validation results demonstrated that the raw materials and processed products in addition to some of the highly processed products can be conveniently authenticated with good sensitivity and precision by this newly proposed approach. Especially, when reference sample mixtures were assayed, these primer sets have still performed well but not the prevailing COI barcoding technology. These could assist in the discrimination and identification of other animal-derived medicines for their form of raw material, the pulverized and the complex.